Increasing Students’ Verb Mastery Through “Puzzle” Game to the Second Grade Students’ at SMA Negeri 4 Halmahera Utara - Amrin Hi. Saban; Nurul Sa’adah Muzayanah; Ida Royani Sabar (Peneliti.net, 2022)
This study aims at increasing students’ verb mastery through “puzzle” game to the second grade at SMA Negeri 4 Halmahera Utara. This research is a quantitative research. The researchers used quantitative research with quasi-experimental design. The populations of this study were 26 students in class XI IPS-1 and 24 students in class XI IPS-2, and the sample taken using random sampling. So the overall samples were 28 students consisted of 18 students in the experimental class and 10 students in the control class. The data collection technique includes pretest, treatment, and post test. The findings of the study showed that most of the students' mastery mastery increased after applying puzzle games in the teaching and learning process. The results of the experimental class analysis showed that the mean pre-test score was 62.5 and the post-test mean score was 72.7 while the control showed that the pre-test mean score was 63.00 and the post-test mean score was 66.00.This indicates that the experimental class experienced increased in verb mastery and hypothesis testing showed that the experimental students' scores were significantly higher than the control class. It can be seen that the t-test value of 0.163 is higher than 0.05 (0.163 <0.05). In addition, the application of puzzle games helps students' ability to memorize and understand new verbs easily.